Evaluation of proximate composition and sensory attributes of composite porridge from finger millet, common beans and carrot flour - Feyera, Milkesa (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Porridge made solely from finger millet does not have better nutritional value. Nutritious and acceptable porridge can be developed by combining finger millet with protein-rich crops like common beans and those high in minerals and vitamins, such as carrots. This study is aimed to develop composite porridge using flour prepared from finger millet, common bean, and carrot. Formulation is computed using the D-optimal mixture design, in which 8% of malted finger millet and 15% of carrot were added to the formulation as fixed levels for enhancement of sensory attributes. The standardized official methods were utilized to evaluate the proximate composition and sensory attributes of developed porridge. The result showed that moisture, ash, protein, crude fat, crude fiber, and utilizable carbohydrate content of composite porridge in percentages were ranged from 9.84±0.07 to 10.6±0.29, 2.82±0.04 to 3.45±0.03, 8.33±0.05 to13.17±0.04, 1.39±0.01 to 1.89±0.01, 8.07±0.05 to 8.86±0.11, 64.24±0.15 to 67.95±0.31, respectively. The present study also found that the color and aroma attributes for finger millet based composite porridge were improved by inclusion of common beans, carrot and sprouted finger millet. Furthermore, texture, and taste did not show significant differences among the composite porridges. According to results of sensory attributes, composite porridge composed of 8% malted finger millet, 70% un-malted finger millet, 7% common bean, and 15% carrot was highly preferable over the other formulations. Incorporating common beans and carrot to finger millet is recommended in the production of composite porridge with improved nutrients and sensory qualities.